We know that any quadratic polynomial can be written as f(x)=ax^2+bx+c , where a, b and c are real numbers. We have following method to factor a quadratic polynomial.
First of all check whether c is positive or negative.
If c is positive.
Step 1: Find the product of a and c. To get product of a and c just multiply a with c.
Step 2: Now get all the factors of the product ac.
Step 3: Find two factors of the product ac such that sum of the two factors is equal to the b i.e. the coefficient of x.
Step 4: Plug in that sum in place of b and simplify to get the factors.
Step 4: Plug in that sum in place of b and simplify to get the factors.
Let us take an example. Consider p(x)=2x^2+5x+3
Compare this polynomial with f(x)=ax^2+bx+c, we get a=2, b=5 \, and \, c=3
Step 1: Product of a and c. 2\times 3=6
Step 2: All the factors of ac i.e. 6 are 1, 2, 3, 6
Step 3: We have to find two factors of 6 such that their sum is equal to b i.e. 5
If we consider factors 2 and 3, we have 2+3=5 and 2\times 3=6
Step 4: We substitute this sum in place of b and simplify to get the factors.
We have p(x)=2x^2+(2+3)x+3
=2x^2+2x+3x+3
=2x(x+1)+3(x+1)
=(x+1)(2x+3)
This is how we get factors of a quadratic polynomial when c is positive.
If c is negative then we follow the following step
We have p(x)=2x^2+(3-2)x-3
=2x^2+3x-2x-3
=x(2x+3)-(2x+3)
=(2x+3)(x-1)
This is how we get factors of a quadratic polynomial when c is negative.
Besides it, we can use box method, or graphic method to find the factors of a quadratic polynomial.
If we put p(x)=0, we get two values for x which satisfy p(x)=0. These two values of x are known as the zeros of the given Quadratic polynomial. Let's take the our first one example p(x)=2x^2+5x+3
Here, the factored form of p(x) is p(x)=(x+1)(2x+3)
And p(x)=0 gives us (x+1)(2x+3)=0
Here, the product of two factors (x+1) and (2x+3) is zero. The product can be zero if either of two is zero. Hence, either x+1=0 or 2x+3=0
Or we can say either x=-1 or x=-\frac{3}{2}
Hence, zeros of p(x)=2x^2+5x+3 are -1 and -\frac{3}{2}
Similarly, we can find the zeros of any quadratic polynomial.
Find the factors of given problems
1. \, 4x^2+14x-8
2. \, 3x^2+10x+7
Find the zeros of the polynomial
1. \, p(x)=3x^2-11x+8
2. \, q(x)=6x^2+9x-6
Compare this polynomial with f(x)=ax^2+bx+c, we get a=2, b=5 \, and \, c=3
Step 1: Product of a and c. 2\times 3=6
Step 2: All the factors of ac i.e. 6 are 1, 2, 3, 6
Step 3: We have to find two factors of 6 such that their sum is equal to b i.e. 5
If we consider factors 2 and 3, we have 2+3=5 and 2\times 3=6
Step 4: We substitute this sum in place of b and simplify to get the factors.
We have p(x)=2x^2+(2+3)x+3
=2x^2+2x+3x+3
=2x(x+1)+3(x+1)
=(x+1)(2x+3)
This is how we get factors of a quadratic polynomial when c is positive.
If c is negative then we follow the following step
Step 1: Find the product of a and c. To get product of a and c just multiply a with c.
Step 2: Now write all the factors of the product ac.
Step 3: Find two factors of the product ac such that difference of the two factors is equal to the b i.e. the coefficient of x.
Step 4: Plug in that difference in place of b and simplify and get the factors.
Step 4: Plug in that difference in place of b and simplify and get the factors.
Let us take an example. Consider p(x)=2x^2+x-3
Compare this polynomial with f(x)=ax^2+bx+c, we get a=2, b=1 \, and \, c=-3
Step 1: Product of a and c. 2\times 3=6
Step 2: All the factors of ac i.e. 6 are 1, 2, 3, 6
Step 3: We have to find two factors of 6 such that their difference is equal to b i.e. 1
If we consider factors 2 and 3, we have 3-2=1 and 2\times 3=6
Step 4: We substitute this difference in place of b and simplify and get the factors.Compare this polynomial with f(x)=ax^2+bx+c, we get a=2, b=1 \, and \, c=-3
Step 1: Product of a and c. 2\times 3=6
Step 2: All the factors of ac i.e. 6 are 1, 2, 3, 6
Step 3: We have to find two factors of 6 such that their difference is equal to b i.e. 1
If we consider factors 2 and 3, we have 3-2=1 and 2\times 3=6
We have p(x)=2x^2+(3-2)x-3
=2x^2+3x-2x-3
=x(2x+3)-(2x+3)
=(2x+3)(x-1)
This is how we get factors of a quadratic polynomial when c is negative.
Besides it, we can use box method, or graphic method to find the factors of a quadratic polynomial.
If we put p(x)=0, we get two values for x which satisfy p(x)=0. These two values of x are known as the zeros of the given Quadratic polynomial. Let's take the our first one example p(x)=2x^2+5x+3
Here, the factored form of p(x) is p(x)=(x+1)(2x+3)
And p(x)=0 gives us (x+1)(2x+3)=0
Here, the product of two factors (x+1) and (2x+3) is zero. The product can be zero if either of two is zero. Hence, either x+1=0 or 2x+3=0
Or we can say either x=-1 or x=-\frac{3}{2}
Hence, zeros of p(x)=2x^2+5x+3 are -1 and -\frac{3}{2}
Similarly, we can find the zeros of any quadratic polynomial.
Find the factors of given problems
1. \, 4x^2+14x-8
2. \, 3x^2+10x+7
Find the zeros of the polynomial
1. \, p(x)=3x^2-11x+8
2. \, q(x)=6x^2+9x-6
No comments:
Post a Comment
Please write your question and answer here